Efficacy of Hydroxyurea in Patients With Sickle Cell Anemia in a Low-Income Country (Côte d’Ivoire) - Kouassi Gustave Koffi; Ruth Dieket; Emeraude N’dhatz; Nelly Eloise Abenan; Alexis Dohoma Silué; Ismael Kamara; Boidy Kouakou; Danho Clotaire Nanho (Anemia)
Conclusion: Hydroxyurea has an important clinical benefit by reducing the incidence of vaso-occlusive events, infections, and transfusions, which translates into fewer hospitalizations. The main problem is that it is not accessible to most of our patients who live in poor socioeconomic conditions.